2019
DOI: 10.5812/modernc.90937
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Psychiatric Disorders in Children and Adolescents of South Khorasan Province in 2017

Abstract: Background: Children and adolescents are the potential capitals of communities. Therefore, their physical, mental, social, and spiritual health is of great importance. Objectives: This study aimed to evaluate the prevalence of psychiatric disorders among children and adolescents in Southern Khorasan province, Iran. Methods: This cross-sectional descriptive-correlational study was conducted in 2017. Study population consisted of children and adolescents aged 6-18 who lived in Southern Khorasan province, Iran. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…This gender-sensitive prevalence of SAD seems to be more preponderant in adolescence and become more moderate along the course of life [49]. However, some studies reported an equal gender distribution in adolescence (i.e., statistically non-significant differences between females and males regarding the prevalence of SAD) [14,30].…”
Section: Introductionmentioning
confidence: 97%
“…This gender-sensitive prevalence of SAD seems to be more preponderant in adolescence and become more moderate along the course of life [49]. However, some studies reported an equal gender distribution in adolescence (i.e., statistically non-significant differences between females and males regarding the prevalence of SAD) [14,30].…”
Section: Introductionmentioning
confidence: 97%